The Impact of Construction Activities on the Stability of Highway Slopes - Baziz, Fouad; Bahloul, Ouassilla; Baziz, Nafissa (Engineering, Technology & Applied Science Research, 2025)
This study concerns the case of a landslide that occurred at kilometer point PK 208 of the East-West Highway in the northeastern part of Algeria, located in the eastern region of Constantine Province. The primary objective is to understand the behavior and mechanisms of this complex landslide phenomenon. The phenomenon’s relationship to various factors that influence this activity, including permanent causes, such as challenging terrain, the geological nature, and the evolving characteristics of the soil under the influence of various climatic conditions or human activities, was investigated. The study examined the impact of the East-West Highway construction at PK 208 on the stability of slopes composed of clayey and marly soils. Field investigations were conducted, and various studies on landslides were analyzed. A monitoring system was employed to track subsurface and surface movements, as well as changes in the groundwater table level. Additionally, numerical modeling using PLAXIS software was performed to evaluate the impact of construction activities, particularly the rise in the groundwater table, on slope stability. The obtained results demonstrated that the position of the groundwater table plays a crucial role in the stability of these structures, underscoring the importance of considering local hydrogeological conditions in the planning and execution of such projects. It is concluded that the complexity of such phenomena in slopes with similar geological, geomorphological, hydrogeological, and geotechnical characteristics is a significant issue that requires particular attention during the planning and execution of such projects.